2001
DOI: 10.1159/000056939
|View full text |Cite
|
Sign up to set email alerts
|

Use of primed in situ labeling (PRINS) for the detection of telomeric deletions associated with mental retardation

Abstract: Rearrangements involving the telomeric regions of human chromosomes are often associated with mental retardation. These rearrangements, however, are difficult to detect using conventional cytogenetic techniques. We propose the use of primed in situ (PRINS) labeling as an alternative to fluorescence in situ hybridization because it is very fast, reproducible, and simple to perform. Sixty-five children with unexplained mental retardation were studied using PRINS technology; two of them were shown to have a telom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Telomere screening by quantitative real-time PCR using SYBR-green I dye has many advantages over other gene dosage techniques, including microsatellite analysis [Reed et al, 1994;Flint et al, 1995;Slavotinek et al, 1999;Colleaux et al, 2001;Rio et al, 2002], FISHtechnique with a subtelomeric probe set [Ning et al, 1996;Knight et al, 1997;, primed in situ labeling [Bonifacio et al, 2001], the recently developed M-TEL assay , the MAPH-technique [Armour et al, 2000;Sismani et al, 2001;Hollox et al, 2002;Gable et al, 2003], the MLPAtechnique [Schouten et al, 2002], and CGH metaphase- [Ghaffari et al, 1998] and CGH array-based hybridizations [Veltman et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Telomere screening by quantitative real-time PCR using SYBR-green I dye has many advantages over other gene dosage techniques, including microsatellite analysis [Reed et al, 1994;Flint et al, 1995;Slavotinek et al, 1999;Colleaux et al, 2001;Rio et al, 2002], FISHtechnique with a subtelomeric probe set [Ning et al, 1996;Knight et al, 1997;, primed in situ labeling [Bonifacio et al, 2001], the recently developed M-TEL assay , the MAPH-technique [Armour et al, 2000;Sismani et al, 2001;Hollox et al, 2002;Gable et al, 2003], the MLPAtechnique [Schouten et al, 2002], and CGH metaphase- [Ghaffari et al, 1998] and CGH array-based hybridizations [Veltman et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to multicolor FISH to detect subtelomeric abnormalities, primed in situ labeling (PRINS) of the telomeric hexamer TTAGGG has been reported to detect two telomeric rearrangements in a series of 65 children with unexplained mental retardation [Bonifacio et al, 2001]. However, it remains to be determined whether detection of the telomeric region itself, rather than the subtelomeric region, can be used to screen for subtelomeric abnormalities, because after chromosome breakage-to prevent the chromosome end from degradation-a novel telomere is formed by a process called telomere healing [Lamb et al, 1993;McEachern et al, 2000].…”
Section: Multicolor Fishmentioning
confidence: 99%
“…The second large group study (5830 cases), using chromosome microarray analysis (CMA), reported a 4.4% abnormality rate [13] . Bonifacio et al found a 3.1% abnormality rate in 65 patients with PRINS [16] . Koolen reported a 6.7% abnormality rate in 210 patients using MLPA [17] .…”
Section: Discussionmentioning
confidence: 96%